Review: Radiation Applications by Hisaaki Kudo - Hayder. K. Obayes (Frontline Social Sciences and History Journal, 2025)
Radiation interacts in unique ways with matter, offering a wide variety of application information that is used by scientists, engineers, architects, and medical professionals to support their work. Over the years, these researchers have improved radiation technologies through their theoretical development, improvements in hardware, and software developments that allow for better corrections for system imperfections. Many of these advances have allowed the application of radiation science to support a wide variety of other applications. These improvements have allowed radiation applications that were once limited to use in large research laboratories to be applied in field and industrial applications.